The Role of Short Video Media in Developing Arabic Listening Skills: A Linguistic Perspective - Nasution, Muhammad Odi Tondi; Hasaniyah, Nur; Anshory, Abdul Muntaqim Al (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
Listening comprehension (maharah istima’) is a fundamental skill in Arabic language learning, yet its mastery often becomes a challenge in pesantren environments that still rely heavily on conventional teaching methods. This study aims to explore the implementation of short video media as an innovative approach to enhance istima’ skills among students at Pesantren Teknologi Majapahit Mojokerto. Employing a qualitative approach with a case study design, data were collected through classroom observations and in-depth interviews with both teachers and students. The findings reveal that the use of short video media positively influences students’ listening skills, particularly in improving pronunciation accuracy, intonation, and contextual understanding. In addition, the integration of short videos fosters greater enthusiasm, motivation, and active participation in the learning process, which are often lacking in traditional pedagogical practices. Despite these benefits, several challenges were identified, including limited technological infrastructure, students’ difficulties in comprehending non-standard Arabic dialects, and restricted vocabulary mastery. These limitations suggest the need for careful content selection, adequate facilities, and continuous teacher training to optimize the effectiveness of short video-based instruction. The contribution of this research lies in highlighting the pedagogical potential of short video media as a practical and adaptive tool for Arabic language learning in pesantren contexts, bridging traditional methods with contemporary technological innovations. Ultimately, this study underscores the importance of integrating media-based approaches to ensure that Arabic learning remains effective, contextual, and aligned with the demands of modern education.